Protective influence of hyaluronic acid on focal adhesion kinase activity in human skin fibroblasts exposed to ethanol - Donejko M; Rysiak E; Galicka E; Terlikowski R; Głażewska EK; Przylipiak A (Dove Medical Press, 2017)
Magdalena Donejko,1 Edyta Rysiak,2 Elżbieta Galicka,1 Robert Terlikowski,3 Edyta Katarzyna Głażewska,1 Andrzej Przylipiak1 1Department of Esthetic Medicine, 2Department of Medicinal Chemistry, Faculty of Pharmacy, 3Department of Health Restoration, Medical University of Białystok, Białystok, Poland Aim: The aim of this study was to evaluate the effect of ethanol and hyaluronic acid (HA) on cell survival and apoptosis in cultured human skin fibroblasts. Regarding the mechanism of ethanol action on human skin fibroblasts, we investigated cell viability and apoptosis, expression of focal adhesion kinase (FAK), and the influence of HA on those processes. Materials and methods: Studies were conducted in confluent human skin fibroblast cultures that were treated with 25 mM, 50 mM, and 100 mM ethanol or with ethanol and 500 µg/mL HA. Cell viability was examined using methyl thiazolyl tetrazolium (MTT) assay and NC-300 Nucleo-Counter. Imaging of the cells using a fluorescence microscope Pathway 855 was performed to measure FAK expression. Results: Depending on the dosage, ethanol decreased cell viability and activated the process of apoptosis in human skin fibroblasts. HA prevented the negative influence of ethanol on cell viability and prevented apoptosis. The analysis of fluorescence imaging using BD Pathway 855 High-Content Bioimager showed the inhibition of FAK migration to the cell nucleus, depending on the increasing concentration of ethanol. Conclusion: This study proves that downregulation of signaling pathway of FAK is involved in ethanol-induced apoptosis in human skin fibroblasts. The work also indicates a protective influence of HA on FAK activity in human skin fibroblasts exposed to ethanol. Keywords: apoptosis, skin fibroblast, focal adhesion kinase, hyaluronic acid, ethanol